Analisis Pengaruh Penggunaan Gadget terhadap Tingkat Konsentrasi Siswa-Siswi Kelas VI SD Siti Aminah Surabaya - Rizki Ramadhan; Diva Cahya Nirwana; Salsabilla Dwi Clarissa; Ayu Wulandari (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
Rapid digital technology growth has integrated gadgets into elementary students' daily routines, raising concerns about concentration amid rising screen time post-COVID-19, particularly at SD Siti Aminah Surabaya where sixth-grade students face academic pressures. This study aims to analyze gadget use's influence on their learning concentration. Employing a quantitative survey design, the population comprised all 30-35 sixth-grade students, with a purposive sample of 25 selected for accessibility and relevance. Data were collected via validated Likert-scale questionnaires measuring gadget frequency/duration and concentration indicators, analyzed using SPSS for simple linear regression including F-test, t-test, R, and R Square. Results indicate no significant influence, with R=0.031, R Square=0.001, F=0.021 (Sig.=0.887), and t=-0.144 (Sig.=0.887), all exceeding 0.05, showing very weak correlation. In conclusion, other factors like environment and supervision dominate, recommending controlled gadget policies for optimal learning.